Gerakan Literasi Sekolah : Sebuah Pengabdian Dosen dan Mahasiswa di SMP Negeri 2 Peukan Bada, Kabupaten Aceh Besar - Razali; Armia; Muhammad Harun (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
Literacy refers to the ability to read, write and see the world and retain information. Libraries strive to support education by providing educational materials, information and reference materials. It was reported that there was a decrease in visits to the library, including at SMP Negeri 2 Peukan Bada in Aceh Besar Regency, Aceh Province. Reusing school libraries requires innovation and concrete steps that are appropriate to the current circumstances and conditions of educational development, especially for students who are likely to be the target of providing education in an interesting way. The aim of this community service is to reopen the SMP Negeri 2 Library during school holidays and holidays to carry out student literacy movements. There are five main types of programs implemented through this service. 1) Demonstration and practice of using Artificial Intelligence/AI applications (artificial intelligence applications) correctly based on scientific standards 2) socialization of artificial intelligence applications (AI/Artificial Intelligence joint learning movements in libraries, 4) short story writing and coloring competitions, 5) donations and book processing. The methods used in delivering the program are lectures, demonstrations and exercises. This activity was attended by 60 students.